Hiasan Bunga Teratai Pada Penjor Galungan Sebagai Teks Etika Sosial Penegakan Dharma - Luh Putu Sri Ariyani (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2022)
Galungan is Hindu holy day. This holy day aims to commemorate the victory of dharma (good) against adharma (evil). Celebration of Galungan uses various ritual tools, such as Penjor - commonly called Penjor Galungan. Penjor Galungan ornaments are very glorious, one of them is lotus. In the postmodern perspective, Penjor Galungan is not only contain of religious values ​​and aesthetics, but it also contains of any aspects beyond the arts, such as social ethos in order to uphold dharma in the society. All of this leads to the achievement of the goal of Hinduism, the happy life both mundane and spiritual.